2011
DOI: 10.1523/jneurosci.6527-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Frontal Lobe Damage Disrupts Value Maximization in Humans

Abstract: Recent work in neuroeconomics has shown that regions in orbitofrontal and medial prefrontal cortex encode the subjective value of different options during choice. However, these electrophysiological and neuroimaging studies cannot demonstrate whether such signals are necessary for value-maximizing choices. Here we used a paradigm developed in experimental economics to empirically measure and quantify violations of utility theory in humans with damage to the ventromedial frontal lobe (VMF). We show that people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 57 publications
7
157
2
Order By: Relevance
“…Brain activity also correlated with willingness to pay in other regions previously associated with decision making and value (Tang, Fellows, Small, & Dagher, 2012), including the OFC (Padoa-Schioppa & Assad, 2006;Wallis, 2007), striatum (Schultz, 2005), and ACC (Kennerley, Walton, Behrens, Buckley, & Rushworth, 2006). Other research has shown that damage affecting the vmPFC and OFC disrupts value-maximizing choices of food stimuli, which further supports a role for these regions in value-based decisions (Camille, Griffiths, Vo, Fellows, & Kable, 2011;Henri-Bhargava, Simioni, & Fellows, 2012). Liking ratings, on the other hand, were primarily correlated with activity in the insula (see the Supplemental Material available online), which has been previously associated with processing the sensory properties of food (de Araujo, Geha, & Small, 2012;Scott & PlataSalaman, 1999).…”
Section: Discussionmentioning
confidence: 63%
“…Brain activity also correlated with willingness to pay in other regions previously associated with decision making and value (Tang, Fellows, Small, & Dagher, 2012), including the OFC (Padoa-Schioppa & Assad, 2006;Wallis, 2007), striatum (Schultz, 2005), and ACC (Kennerley, Walton, Behrens, Buckley, & Rushworth, 2006). Other research has shown that damage affecting the vmPFC and OFC disrupts value-maximizing choices of food stimuli, which further supports a role for these regions in value-based decisions (Camille, Griffiths, Vo, Fellows, & Kable, 2011;Henri-Bhargava, Simioni, & Fellows, 2012). Liking ratings, on the other hand, were primarily correlated with activity in the insula (see the Supplemental Material available online), which has been previously associated with processing the sensory properties of food (de Araujo, Geha, & Small, 2012;Scott & PlataSalaman, 1999).…”
Section: Discussionmentioning
confidence: 63%
“…Such anticipatory activity is thought to explain the role this area plays in a variety of behaviors (Camille, Griffiths, Vo, Fellows, & Kable, 2011; Gallagher, McMahan, & Schoenbaum, 1999; Gourley et al, 2013; Izquierdo, Suda, & Murray, 2004; Jones et al, 2012; Ostlund & Balleine, 2007; Reber et al, 2017). However, the OFC is also often important for learning (Jones & Mishkin, 1972; McDannald, Lucantonio, Burke, Niv, & Schoenbaum, 2011; McDannald, Saddoris, Gallagher, & Holland, 2005; Takahashi et al, 2009; Tsuchida, Doll, & Fellows, 2010; Walton, Behrens, Buckley, Rudebeck, & Rushworth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The situation is more balanced with lesions to the ventromedial prefrontal cortex, in keeping with the putative role of this region in integrating appetitive and aversive dimensions. Such a lesion was shown to affect information integration in multi-attribute decision-making [93], to amplify inconsistencies in choices between appetitive food items [94], but also to impair learning from negative feedback [95]. …”
Section: Box 1 Effects Of Focal Lesions On Appetitive Versus Aversivementioning
confidence: 99%